ANALISIS JARINGAN KERJA DAN PENENTUAN JALUR KRITIS DENGAN CRITICAL PATH METHODE-CPM (STUDI KASUS PEMBANGUNAN PENDOPO BALAI ADAT PROVINSI JAMBI) - Elvira Handayani (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
Time management is a necessary part of the process to ensure project completion time. Time management system centered on whether or not the running project scheduling, wherein the scheduling has provided specific guidelines for completing the project activity more quickly and efficiently. One of the projects is the scheduling of network planning using critical path method (CPM). Use of CPM can find activities that should not be delayed, and if delayed causing project delays. In the customs hall pavilion construction project Jambi province with 79 critical path of activities through which there were 33 work items.keyword:  Scheduling with CPM network diagram